Effect of hexane extract of Clinacanthus nutans leaves on HSC-3 cells migration in vitro - Roeslan, Moehamad Orliando; Qurrotuain, Noni Anis; Rahmawati, Dicha Yuliadewi; Monthanpisut, Paopanga Orliando (Majalah Kedokteran Gigi Indonesia, 2023)
Cancer is a major health issue and considered the most life-threatening disease worldwide. The oral cavity is one of the top ten locations in the body most frequently affected by cancer. The most common type of oral cancer (90%) is squamous cell carcinoma. Leaves of C. nutans have many uses and benefits, one of which is its potential as an anticancer agent. This study aims to determine the effect of C. nutans leaves hexane extract on HSC-3 cell strain migration. The leaves of C. nutans were extracted using a hexane solvent with the maceration method. Various concentrations (500, 250, 100, 50 and 25 mg/mL) were assessed to identify the effect of C. nutans leaves hexane extract on HSC-3 cells migration at 0, 6, 12, 24 and 48 time point. The concentration of 500 μg/mL was found to possess the ability to inhibit migration and induce apoptosis by the 6th hour. The concentration of 250 μg/mL induced apoptosis by the 24th hour. Concentrations of 100 μg/mL and 50 μg/mL were capable of inhibiting cell migration, and the concentration of 25 μg/mL could only delay cell migration up to the 12th hour. In conclusion, hexane extract of C. nutans leaves can inhibit HSC-3 cells migration.